Abnormal distribution of AQP4 in minor salivary glands of primary Sjögren’s syndrome patients - Margherita Sisto; Loredana Lorusso; Giuseppe Ingravallo; Beatrice Nico; Domenico Ribatti; Simona Ruggieri; Dario Domenico Lofrumento; Sabrina Lisi (Autoimmunity, 2017)
A decreased saliva production occurs in primary Sjögren’s syndrome (pSS), an autoimmune disease characterized by oral and ocular dryness due to dysfunction of the lacrimal and salivary glands (SGs). Since water movement is involved in saliva secretion, the expression, localization, and function of the water channels aquaporins (AQPs) have been extensively studied in SGs. To date, the presence of AQP4 remains controversial and ambiguous in human SGs. We investigated by immunohistochemistry, high-resolution confocal microscopy and quantitative image analysis, Western blot and real-time RT-PCR, the presence of the AQP4 gene, and the distribution of AQP4 protein in healthy controls and pSS SG biopsies. Through the immunohistochemical analysis, we demonstrated that AQP4 presence is confined to the basal region of acini, to the lateral and apical membrane of intercalated and striated ducts in both control and pSS glands. The most striking observation was the discovery of AQP4 localization in myoepithelial cells (MECs) that surround acini lobules and intercalated ducts, and the demonstration of AQP4-downregulated immunoreactivity in pSS MECs. Our studies suggest that the capacity for water flow across the membrane of MECs may be altered in pSS, identifying AQP4 as a promising new therapeutic agent to treat xerostomia.